IMPLEMENTASI BLENDED LEARNING DALAM MATA KULIAH ULUMUL QUR’AN PADA PASCASARJANA UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR - Achmad Abubakar Achmad; Ahmad Yani; Abdul Syatar (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2021)
This study aims to see the implementation of blended learning in Ulumul Qur'an courses at uin Alauddin Makassar Postgraduate. The method used in this study uses a type of qualitative research related to the implementation of Blended Learning Courses Ulumul Qur'an at the Postgraduate UIN Alauddin Makassar. The results showed that: (1) the description of the model of implementation of the implementation of the study blended Ulumul Qur'an courses at the Postgraduate UIN Alauddin Makassar using a dual-system that is a combination of conventional systems with online. More use of online learning systems during the Pandemic (80%) compared to traditional face-to-face learning systems. The merger of the two systems includes the incorporation of learning resources as well (learning modules, textbooks, and journals), the implementation of learning (online discussions, watching videos, and accessing supporting resources, and the incorporation of a learning evaluation system, including standardized assessment through quizzing, midterm exams, and final exams. (2) the results of the implementation of blended learning in Ulumul Qur'an courses are illustrated from five main aspects, namely (a) increased utilization of various sources, (b) increased active participation, (c) increased ability to construct knowledge, (d) activation of feedback, and (e) improvement of academic achievement